On the Development of Islamic Jurisprudence - Murad Wilfried Hofmann (International Institute of Islamic Thought, 1999)
This article examines the state of Islamic jurisprudence with regard to many sensitive issues, such as the status of women and minorities in Islam, Islam and Democracy, hudud punishments. The author explores the current state of Islamic discourse on jurisprudence and identifies three approaches-traditional, secular and reformist. The paper explores the positions of the traditional ulama and the reformist mujtahids on the mentioned topics and finds the reformist position more sensible and closer to the position of ihe Qur'an and Sunnah. This paper while advocating neo-ijtihad, makes an impressive case for the merits and Islamic credibility of the reformist jurisprudence.